EFEKTIVITAS LEAN SIX SIGMA TERHADAP KINERJA PERUSAHAAN : TINJAUAN LITERATUR SISTEMATIS - Agustina, Nunsy; Aryani, Putri Dwita; Gandasari, Nyimas Aulia; Ramadhani, Dwi Putri Andika; Aulia, Syifa Nisa; Relasari, Relasari (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to analyze the effectiveness of Lean Six Sigma implementation on company performance in the manufacturing industry sector. The theory used in this study is contingency theory. Researchers examined 21 articles with a time span of 2020-2025 taken from the Scopus, PubMed and Google Scholar databases through Publish or Perish (PoP) software. The results of the study show that Lean Six Sigma with the DMAIC methodology has a significant impact on increasing operational efficiency, reducing production defects, and improving output quality in the manufacturing industry. Each stage of DMAIC uses various tools designed to identify, analyze, and resolve problems in the production process.